2020
DOI: 10.1021/acs.langmuir.0c00130
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Adhesion and Biofilm Formation on Polydimethylsiloxane are Independent of Substrate Stiffness

Abstract: Bacterial adhesion and biofilm formation on the surface of biomedical devices is a detrimental process that compromises patient safety and material functionality. Several physicochemical factors are involved in biofilm growth, including the surface properties. Among those, material stiffness has recently been suggested to influence microbial adhesion and biofilm growth in a variety of polymers and hydrogels. However, no clear consensus exists about the role of material stiffness on biofilm initiation and wheth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The wrinkled topography on PDMS surfaces significantly reduced both E. coli adhesion and the overall biofilm biomass, regardless of material stiffness. This result suggests that topographical patterns of surfaces may render surface stiffness negligible regarding bacterial adhesion and biofilm accumulation (Arias et al, 2020). Another example of the interdependence of surface parameters that affect bacterial adhesion can be found in a recent study by Yuan et al (2017).…”
Section: Complex Surface Propertiesmentioning
confidence: 87%
See 1 more Smart Citation
“…The wrinkled topography on PDMS surfaces significantly reduced both E. coli adhesion and the overall biofilm biomass, regardless of material stiffness. This result suggests that topographical patterns of surfaces may render surface stiffness negligible regarding bacterial adhesion and biofilm accumulation (Arias et al, 2020). Another example of the interdependence of surface parameters that affect bacterial adhesion can be found in a recent study by Yuan et al (2017).…”
Section: Complex Surface Propertiesmentioning
confidence: 87%
“…As discussed earlier, surface stiffness and topography are the factors interdependently affecting bacterial adhesion. Interestingly, Arias et al (2020) found that E. coli tend to adhere on PDMS surfaces with variable stiffness in a different pattern when surface topography was introduced to the surface. The wrinkled topography on PDMS surfaces significantly reduced both E. coli adhesion and the overall biofilm biomass, regardless of material stiffness.…”
Section: Complex Surface Propertiesmentioning
confidence: 99%
“…The inhibition of gram-negative bacterial adhesion to PH coating was relatively close to the inhibition of bacterial adhesion to others antifouling materials (≈48-58%). [111][112][113] Antifouling materials containing silver nanoparticles (3.5 wt%) [114] or amphiphilic coating with low surface energy (≈20 mJ m −2 ) [115] displayed a larger inhibition of bacterial adhesion (≈88-90%) but did not possessed an anticorrosion property.…”
Section: Resultsmentioning
confidence: 99%
“…Formalinfixed E. coli seeded on wrinkled polydimethylsiloxane (PDMS) was imaged with a PNP-TR cantilever in contact mode in PBS using a force of 20 pN, and subsequently indented with a trigger force of 2 nN following a procedure as described previously. Wrinkled PDMS was obtained as described by Arias and coworkers 56 . Determination of the nanoprobes' radius was performed using a calibration grid (Silicon grating TGT01, NT-MDT Spectrum Instruments) ( Supplementary Figures S5 and S6).…”
Section: Methodsmentioning
confidence: 99%